The Cambridge handbook of new human rights : recognition, novelty, rhetoric / edited by Andreas von Arnauld, Kerstin von der Decken, Mart Susi. - Arnauld, Andreas von; Susi, Mart, 1965-; Decken, Kerstin von der (Cambridge University Press, 2020)
The book provides in-depth insight to scholars, practitioners, and activists dealing with human rights, their expansion, and the emergence of 'new' human rights. Whereas legal theory tends to neglect the development of concrete individual rights, monographs on 'new' rights often deal with structural matters only in passing and the issue of 'new' human rights has received only cursory attention in literature. By bringing together a large number of emergent human rights, analysed by renowned human rights experts from around the world, and combining the analyses with theoretical approaches, this book fills this lacuna. The comprehensive and dialectic approach, which enables insights from individual rights to overarching theory and vice versa, will ensure knowledge growth for generalists and specialists alike. The volume goes beyond a purely legal analysis by observing the contestation, rhetorics, the struggle for recognition of 'new' human rights, thus speaking to human rights professionals beyond the legal sphere.